Analysis of The Influence of Financial Reporting Characteristics and Success of Budget Controlling on Transparency of Regional Government Financial Reports - Erny Rachmawati; Andoko; Friyan Satria; Frinan Satria; Rahmatya Widyaswati (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
The purpose of this study is to investigate how budgetary management and the features of regional financial reports affect the openness of government financial reports. Employees of the Regional Revenue and Asset Financial Management Office in Province who worked in Regency and City Offices were the study's respondents. Employees from three districts and three cities in one province in Indonesia made up the study's sample. Convenient sampling was used as the study's sampling technique, while multiple regression analysis was employed as the study's data processing technique. The findings indicated that budget control has an effect on government financial report transparency with a significant value of less than 0.05 and regional financial report characteristics have an effect on government financial report transparency, and budget control and regional financial report characteristics have an effect simultaneously.